The Effectiveness of Using Student Worksheets in Science Learning on Student Learning Outcomes - Fajriani Chutami; Suhartini Suhartini (Postgraduate, University of Mataram, 2021)
This study aims to re-analyze the effectiveness of the use of Student Worksheets in science learning on student learning outcomes. The method used in this study is a meta-analysis conducted by reviewing, summarizing, and analyzing research data from several studies that have been conducted. Previously there was a way to browse articles contained in journals that could be accessed online through Google Scholar. This meta-analysis research uses a sample of 10 relevant articles in related national journals about Student Worksheets in science learning. This meta-analysis shows that based on the calculation of the effect size, there is an effect of the use of Student Worksheets in science learning on student learning outcomes. There are two studies that have an effect size with a very high category, namely 1.336 and 1.140, three studies have an effect size with a high category, namely 0.995, 0.935, and 0.911, and five studies that have an effect size in the medium category with a range of 0.419 to 0.735